Pressure broadening in Raman spectra of CH4–N2, CH4–CO2, and CH4–C2H6 gas mixtures - Tanichev, Aleksandr S.; Petrov, Dmitry V. (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2023)
[Display omitted] •A simple method to stimulate the Raman bands of CH4, N2, CO2, and C2H6 in natural gas.•N2–, CO2–, and C2H6-broadening coefficients averaged by J for the ν2 Raman band of CH4.•Methane accelerates the collapse of the Q branch of N2 but slows it down in C2H6. Different molecular environments change the spectrum of a given gas sample involved in a mixture compared to the spectrum of a pure gas. It is necessary to account for this effect to improve the accuracy of the analysis of the natural gas composition by Raman spectroscopy. First, the change in the main components of natural gas (methane, nitrogen, carbon dioxide, and ethane) must be considered. This work is devoted to the mutual influence of CH4–N2, CH4–CO2, and CH4–C2H6 on their characteristic Raman bands in the range of 300–2500 cm−1. The half-width and asymmetry of the Q branches of N2, CO2, and C2H6 as a function of methane concentration were obtained in the range of 1–50 bar. The averaged broadening coefficients of the rotational-vibrational lines of the ν2 band of CH4 perturbed by N2, CO2, and C2H6 are measured. A high-sensitivity spectrometer with a resolution of 0.5 cm−1 based on spontaneous Raman scattering was used to obtain reliable results. The algorithm and all the necessary parameters for simulating the effect of various molecular environments on the Raman bands of the main components of natural gas are presented.